Use of Gel Permeation Chromatography in Studies of Acacia Polyacantha Gum - Omer, Elgaili. A.; Abdulaziz, Mohammed. E.; Osman, Mohammed . E.; Hassan, Elfatih. A., (Gezira Journal of Engineering and Applied Sciences, 2018)
Fractionation of Acacia polyacantha gums(Kakamut) using a gel permeation column coupled to a multi – detector system comprising light scattering, refractive index and UV detector gave an insight in the molecular mass of the gum molecules. The resultant chromatograms showed a high molecular weight(Mw) fraction associated with much of the protein present in the polymer molecule, a low molecular mass fraction of much lesser amount of protein and low molecular mass proteinaceous fraction. The molar mass distribution pattern produced for A. polyacantha differed from that obtained for A. senegal gum. However the patterns of the two types of gums differed in the proportion of each fraction. Comparison of three A. polyacantha  gum samples revealed that the Layoon soil samples (Layoon forest) showed, a higher Mw fraction (32%) than the  samples of the clay soil (Abugarin and Gargadah) 30% and 20%, respectively.